Effect of Platelet Age on Adhesiveness to Collagen and Platelet Surface Charge - Castellan, Robert M.; Steiner, Manfred (Thrombosis and Haemostasis, 1976)
Adhesion to collagen was investigated as a function of platelet age in rat platelets. Platelet adherence was measured using EDTA-containing platelet- rich plasma which was added to preparations of collagen fibers clamped between magnetic stirrers by recording changes in light transmission. The plot of light transmission versus logarithm of time was linear and allowed calculation of a slope factor which related to the rate of adherence. Neither the amount of collagen nor the platelet count were limiting in the test. Young platelet populations (≤ 1 day old) were obtained during the recovery phase from immune induced thrombocytopenia. Old platelet populations were prepared by blocking thrombopoiesis with cyclophosphamide. Young platelets showed a moderate but statistically significant increase in adhesivity to collagen but old platelets did not differ significantly from randomly aged platelets in this function. The electrophoretic mobility of platelets was not affected by their age.